KUALITAS FISIK DAN KIMIA DEDAK PADI YANG DISIMPAN MENGGUNAKAN TEPUNG KULIT MANGGIS(Garcinia mangostana linn) PADA LEVEL BERBEDA - Tabita Naomi Ralahalu; Shirley Fredriksz; Sandri Tipka (Jurusan Peternakan Fakultas Pertanian Universitas Pattimura, 2020)
The problem in using rice bran as animal feed is its low stability due to rancidity of hydrolysis and rancidity of oxidation. In addition, it quickly becomes clumpy and brings in insects, especially lice. The objective of this research was to determine the level of use of mangosteen peel flour in rice bran storage for one month on the physical and chemical qualities of rice bran. The research was conducted at the Laboratory of Animal Nutrition and Forage, Department of Animal Husbandry, Faculty of Agriculture, Pattimura University, Ambon. The materials used are rice bran from Gemba and mangosteen peel. The equipment used is a plastic sack with a size of 5 kg, a digital scale, a blender, a temperature and humidity measuring device. The research was conducted using a completely randomized design (CRD), 4 x 4. The observed variables included weight, color, odor, moisture content, crude protein, fat, and peroxide number. The follow-up test used if the treatments show significant differences is the Duncan test. The treatments tested were DKM0 = rice bran without mangosteen peel flour; DKM1 = rice bran with 5% mangosteen peel flour; DKM2 = rice bran with 7.5% mangosteen peel flour; DKM3 = Rice bran with 12.5% ​​mangosteen peel flour. The peroxide value of 7.95meq / kg is achieved when using 5% mangosteen peel flour, while at the 10% level it can suppress the smell until it becomes slightly rancid. The use of 15% mangosteen peel flour was not significant for color, fungus, protein moisture, fat and peroxide numbers.